2015
DOI: 10.1007/s11019-015-9624-y
|View full text |Cite
|
Sign up to set email alerts
|

Autonomy in place of birth: a concept analysis

Abstract: This article examines one of the relevant concepts in the current debate on home birth-autonomy in place of birth-and its uses in general language, ethics, and childbirth health care literature. International discussion on childbirth services. A concept analysis guided by the model of Walker and Avant. The authors suggest that autonomy in the context of choosing place of birth is defined by three main attributes: information, capacity and freedom; given the antecedent of not harming others, and the consequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…The model was developed through a concept analysis in order to understand women’s choices regarding place of birth, and it can be transferred to the choice regarding mode of birth. In light of the results found in these thematic syntheses, the problem about performing CS upon maternal request could be embedded between the concepts ‘Do no harm’ and ‘Take responsibility for the outcome’, discussed in terms of Information, Capacity , and Freedom [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The model was developed through a concept analysis in order to understand women’s choices regarding place of birth, and it can be transferred to the choice regarding mode of birth. In light of the results found in these thematic syntheses, the problem about performing CS upon maternal request could be embedded between the concepts ‘Do no harm’ and ‘Take responsibility for the outcome’, discussed in terms of Information, Capacity , and Freedom [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Freedom of choice is an essential and delicate component of autonomy that might be internal or external. Laws, regulations, and traditions might restrict external freedom, while internal freedom could be restricted by, e.g., anxiety [ 45 ]. There are some ethical aspects connected to freedom of choice.…”
Section: Discussionmentioning
confidence: 99%
“…Being able to exercise reproductive rights and, particularly, to determine how and where to give birth qualifies as reproductive autonomy [ 20 ]. Similarly, a concept analysis on autonomy in place of birth emphasized that being capable of choosing place of birth in the absence of coercion is one prerequisite for an autonomous choice [ 21 ]. Finally, emphasizing the imperative to enable women to make reasonable choices, a Cochrane review on place of birth has pointed out that women residing in areas where they are not well informed about possible places of birth “may welcome ethically well‐designed trials that would ensure an informed choice” [ 22 , p2].…”
Section: Introductionmentioning
confidence: 99%
“…Autonomy presumes that a person has experience, education, self‐discipline and decision‐making capacity (Keenan, ). Recently, it was suggested that information, capacity and freedom were the attributes for autonomy in the context of choosing a place to give birth (Halfdansdottir et al., ). Referring to autonomy in relation to patients in high‐tech care environments could be seen as paradoxical, as in most cases, they are vulnerable and could lack physical and/or metacognitive capacity (Levinsson, ), thus prohibiting them from remaining or becoming autonomous.…”
Section: Introductionmentioning
confidence: 99%